(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The right of access to palliative care and pain relief is recognized and protected in the context of the essential assistance levels, in order to ensure “respect for the dignity and the autonomy of each person, the need for health, equity in access to assistance, the quality of care and its appropriateness with regard to specific needs”. The legal system has to guarantee this right providing adequate means to relieve from suffering. However, it is from the data provided by the regions, in this sector and considering the means provided by them, that emerges a picture characterized by lights and shadows.